2011
DOI: 10.1292/jvms.10-0397
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Development of Hypoplastic Thymus in Semi-Lethal Dwarf pet/pet Males

Abstract: ABSTRACT. The petit rat (pet/pet) is a new semi-lethal dwarf mutant with anomalies in the thymus and testes, defects inherited as a single autosomal recessive trait. At birth, these pet/pet rats show low birth weight and extremely small thymuses; at 140 days of age, their thymuses show abnormal involution. In the present study, we examined early postnatal development of hypoplastic pet/pet thymuses. In addition to being hypoplastic at birth, pet/pet thymus growth was almost completely impaired during the early… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We characterized the phenotype of affected offspring rats and named the strain DEK. The pet locus is responsible for dwarfism, thymus hypoplasia, and postnatal semilethality [14, 15]. We mapped the locus on rat chromosome 9 using microsatellite markers and confirmed that the DEK phenotype is independent of the pet genotype (data not shown).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…We characterized the phenotype of affected offspring rats and named the strain DEK. The pet locus is responsible for dwarfism, thymus hypoplasia, and postnatal semilethality [14, 15]. We mapped the locus on rat chromosome 9 using microsatellite markers and confirmed that the DEK phenotype is independent of the pet genotype (data not shown).…”
Section: Discussionmentioning
confidence: 65%
“…All rats were housed in conventional conditions under a 14 : 10 h light : dark cycle with ad libitum access to water and standard chow (CR-LPF, Oriental Yeast Co. Ltd., Tokyo, Japan). Room temperature and humidity were maintained at 20 ± 2°C and 50 ± 10%, respectively [14, 15]. Their body weight was measured weekly, with nonfasting blood glucose levels measured between 1 and 7 pm at the ages of 5, 10, 15, 22, and 30 weeks.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation